EFEKTIVITAS FORMASI TEMPAT DUDUK LATER “U” TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SD - Anggraina, Yulia Angga; Saputro, Anip Dwi; Sumaryanti, Lilis (Jurnal Gentala Pendidikan Dasar, 2025)
The purpose of this study was to determine the effectiveness of later “U” seating formation on Indonesian language learning outcomes of fourth grade students at SD Muhammadiyah Ponorogo. This research is focused on quasi-experimental design. The research instruments used were Pre-Test and Post-Test questions. In this study using data analysis techniques Normality Test, Homogeneity Test, and Hypothesis Test. Based on the t test, it is known that the average pre-test value is 71.18 or 71.18% after the post-test is 95.04 or 95.04% so that the increase is 23.86 or 23.86%. Based on the test results, the average value of the control class was 89.29 while the average value of the experimental class was 95.04, so that from the final data analysis obtained tcount = 2.861 while ttable = 2.004, because the value of tcount> ttable then significance and the proposed hypothesis can be accepted, so the result is “there is a difference in students' Indonesian learning outcomes when before and after using the later U seating formation”.